Closing the Gender Gap in Extractives : What Has Been Done and What Have We Learned? - Parks, Rachel Bernice (World Bank, Washington, DC, 2018)
Women are not receiving equal benefits of the global development of oil, gas, and mineral resources, even as they shoulder a greater burden of the negative impacts. Not only are men consulted more than women in the project-planning process, but men's access to subsequent economic benefits is much greater. The World Bank is supporting efforts to increase gender equality at every phase of development of extractive industries by removing constraints for more and better jobs for women, dismantling barriers to women's ownership and control of assets, and enhancing women's voices and agency.